Uji Bakteri Simbiotik dan Nonsimbiotik Pelarutan Ca vs. P dan Efek Inokulasi Bakteri pada Anakan Turi (Sesbania grandiflora L. Pers.) - Widawati, Sri (JURNAL BIOLOGI INDONESIA, 2015)
ABSTRACTNitrogen-fixing bacteria that dissolve phosphate and produce IAA (plant growth hormones) are useful for biological organic fertilizer (BOF). Thirty nitrogen-fixing isolates have been isolated from the rhizosphere soil on Mount Salak, Bogor. This study aims to find nitrogen-fixing symbiotic and non-symbiotic bacteria that could potentially dissolve phosphorus (P) and produce hormones IAA. The N-fixing bacteria were tested to promote growth of turi (Sesbania grandiflora) duringÂ  seedling. Turi is called astringency tree, because the entire tree is useful for land reclamation, produce tannin, gum, resin, vegetables, medicine, tonic, antipyretic, and as pulp material. Pikovskaya medium was used to evaluate the ability of nitrogen-fixing bacteria to dissolve phosphate. The effect of bacteria on the growth of seedlings Sesbania grandiflora were evaluated using pot experiment. Pot contained sterile sand were arranged as factorial with 3 replications and watered with sterile distilled water containing Muller solution in the green house. The results showed that, the highest populations of bacteria, P solubilization index, and PMEase produced by Rhizobium, Azotobacter and Azospirillum were isolated from the rhizosphere of tea plant. The isolates were identified as Azotobacter chrococcum and Azospirillum lipoferum and Rhizobium sp. All of the isolates produced plant growth hormon (IAA). Effects of inoculants ABC (Azospirillum, Azotobacter, Rhizobium 1), ABD (Azospirillum, Azotobacter, Rhizobium 2), BCD (Azotobacter, Rhizobium 1, Rhizobium 2), dan ABCD (Azospirillum, Azotobacter, Rhizobium 1, Rhizobium 2), were very good on growth of Turi plant seedlings. All isolates formed root nodules, except the ABD and D isolats.Â Keywords: Nitrogen fixing bacteria, Phosphate solubilizing bacteria, Sesbania grandiflora L.Pers.Â